A Review of Borderline Personality Disorder in Adolescence - Irawan, Muhammad Renaldi (Lombok Medical Journal, 2023)
Personality instability in adolescence that develops into BPD, can make adolescents experience long-term impairment conditions that can reduce the quality of social life, education and work in the future. Borderline Personality Disorder (BPD) is a condition where a person experiences a personality disorder characterized by emotional or mood instability, behavior, self-image and impulsive behavior that is difficult to control by showing symptoms of at least 5 of the 9 diagnostic criteria. It is said to be borderline or threshold because people with this disorder do not meet the characteristics of either neurosis or psychosis, so it is considered to be in between the two conditions. The cause of BPD is unclear, but it is thought to be the result of genetic, psychosocial and neurobiological factors that influence brain development. Therapeutic modalities that can be given to people with BPD include Dialectical Behavioral Therapy (DBT), Mentalization-Based Treatment (MBT), Transference-Focused Psychotherapy (TFP), and Schema-Focused Therapy (SFT).